Platynosomum fastosum-induced Infections in Domestic Shorthair Cats: a Retrospective Study of Seven Cases - Headley, Selwyn A.; Ferioli, Raquel B.; Reis, Antônio C. F.; Bracarense, Ana Paula F. R. L. (Brazilian Journal of Veterinary Pathology, 2011)
The clinical and the pathological findings associated with Platynosomum fastosum-induced infections are described in Domestic shorthair cats by the retrospective analyses of archival records. Icterus was the most predominant clinical alteration observed; three cats demonstrated clinical manifestations of hepatic encephalopathy. The laboratory findings of two cases confirmed severe hepatic dysfunction due to elevations in the serum concentrations of alanine aminotransferase, phosphatase alkaline, and gamma-glutamyl transferase. Hypertrophy of bile ducts occurred in all animals. All cats demonstrated adenomatous hyperplasia of biliary epithelium and/or periductal fibrosis associated with intraductal trematode and/or intralesional ova of P. fastosum. One cat had pathological alterations consistent with cystic mucinous hyperplasia and gallbladder mucocele associated with intralesional ova of P. fastosum, while dilated cystic intra-hepatic structures associated with chronic platynosomiasis occurred in another cat. Platynosomiasis was an incidental finding in one cat.